Analisis Gaya Kepemimpinan Kepala Sekolah Dasar Gugus II Kecamatan Tanete Riattang Barat Kabupaten Bone - Alwasia; Muhammad Faisal; Wahira (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study is a qualitative study that aims to analyze the leadership style of school principals in Cluster II, Tanete Riattang Barat District, Bone Regency. Based on the formulation of the problem and the results of the study, it can be concluded that the leadership style most widely applied by school principals in Cluster II, Tanete Riattang Barat District, Bone Regency is democratic or deliberation. This means that school principals tend to involve teachers and staff in the decision-making process. This reflects an effort to create a participatory and collaborative school environment. A democratic leadership style has great potential to improve the quality of education in schools. However, its implementation requires commitment and ongoing efforts from all parties involved. By considering supporting factors and overcoming existing obstacles, schools can create a more democratic, participatory, and effective learning environment..